Author Correction: Genome-wide analysis of multi- and extensively drug-resistant Mycobacterium tuberculosis - Coll, Francesc (2018)
This deposit is composed by a publication in which the IGC's authors have had the role of collaboration (it's a collaboration publication). This type of deposit in ARCA is in restrictedAccess (it can't be in open access to the public), and can only be accessed by two ways: either by requesting a legal copy from the author (the email contact present in this deposit) or by visiting the following link: https://www.nature.com/articles/s41588-018-0074-3